Modular Synthesis and Antiproliferative Activity of New Dihydro-1H-pyrazolo[1,3-b]pyridine Embelin Derivatives - Pedro Martín-Acosta; Ángel Amesty; Miguel Guerra-Rodríguez; Borja Guerra; Leandro Fernández-Pérez; Ana Estévez-Braun (MDPI AG, 2021)
A set of new dihydro-1H-pyrazolo[1,3-b]pyridine and pyrazolo[1,3-b]pyridine embelin derivatives was synthesized through a multicomponent reaction from natural embelin, 3-substituted-5-aminopyrazoles and aldehydes. The synthesized compounds were evaluated against three hematologic tumor cell lines, HEL (acute erythroid leukemia), K-562 (chronic myeloid leukemia) and HL-60 (acute myeloid leukemia), and five breast cancer cell lines (SKBR3, MCF-7, MDA-MB-231, BT-549, HS-578T). The primate non-malignant kidney Vero cell line was used as the control of cytotoxicity. From the obtained results, some structure-activity relationships were outlined. Furthermore, in silico prediction of physicochemical properties and ADME parameters were determined for the derivatives with the best antiproliferative values.